IMPACT OF DATA PROTECTION REGULATION UPDATES ON CYBERSECURITY IN FINANCIAL INSTITUTIONS - Gunawan Widjaja; Hotmaria Hertawaty Sijabat (Jurnal Komunikasi, 2025)
This study aims to evaluate the impact of data protection regulation updates on cybersecurity in financial institutions. Stricter regulatory updates have encouraged financial institutions to adopt better security measures, such as data encryption, intrusion detection, and stricter access control, which significantly improve the security of customer data. However, the process of adjusting to the new regulations also poses significant technical and operational challenges, including the need for significant investment in technology and staff training. On the other hand, the implementation of this regulation has the potential to increase customer confidence in financial institutions, as customers feel that their data is properly managed and secure. Thus, the update of this data protection regulation not only has an impact on improving cybersecurity, but also opens opportunities for financial institutions to strengthen relationships with customers and gain a competitive advantage in the industry